Protective effects of kolaviron and quercetin on cadmium-induced testicular damage and endocrine pathology in rats (2012)
This study evaluated the effects of kolaviron, a biflavonoid from Garcinia kola seed, and quercetin on cadmium-induced reproductive toxicity in rats. Adult male rats were administered with either cadmium (15 mg kg _1) alone or in combination with kolaviron (200 mg kg_1) or quercetin (10 mg kg_1) daily for 5 days. Cadmium-treated rats showed (P < 0.05) decrease in the body weight gain, testis and epididymis weights. However, upon co-administration of kolaviron or quercetin, these changes were significantly reversed in cadmium- treated rats. Also, administration of kolaviron or quercetin significantly prevented cadmium-mediated decrease in sperm motility and epididymal sperm concentration and reversed the increased level of sperm abnormality to near control. In testes and sperm, cadmium treatment resulted in significantdecrease in the activities of superoxide dismutase, catalase and glutathione peroxidase, whereas it increased glutathione S-transferase activity as well as hydrogen peroxide and malondialdehyde levels. While plasma levels of triiodothyronine and tetraiodothyronine remained unaffected, the levels of testosterone, luteinising hormone and follicle stimulating hormone were decreased in cadmium-treated rats. Cadmium treatment caused mild congestion of interstitial vessels and oedema in the testes. Taken together, kolaviron and quercetin inhibited the adverse effects of cadmium on the antioxidant enzymes, markers of oxidative stress, endocrine and testicular structure in rats.